The Relationship between nutritional status and anaemia incidence in adolescent girls at Posyandu Remaja Mojo Gubeng Surabaya : Hubungan Status Gizi Dengan Kejadian Anemia Pada Remaja Putri Di Posyandu Remaja Mojo Gubeng Surabaya - Rahmat, Tsamara; Rini Purbowati; Wulandari, Atik Sri (Calvaria Medical Journal, 2026)
Background: Anaemia is a global health problem frequently occurring among adolescent girls due to increased iron demands and menstrual cycles. Objective: This study aimed to analyse the association between nutritional status based on Body Mass Index (BMI) and anaemia incidence in adolescent girls at Posyandu Remaja Mojo Gubeng Surabaya. Methods: A cross-sectional quantitative study was conducted with 40 respondents selected by total sampling. Bivariate analysis used Fisher's exact test (α = 0.05). Results: BMI distribution: normal 47.5%, underweight 32.5%, overweight 20.0%. Anaemia prevalence was 27.5%, highest in the underweight group (61.5%). A significant association was found between nutritional status and anaemia (p = 0.004). Conclusion: Nutritional status was significantly associated with anaemia among adolescent girls. Underweight adolescents had a higher risk of anaemia. Integrated nutrition interventions at the Posyandu level are recommended.